Winter Bees & Other Poems of the Cold - Sidman, Joyce (Houghton Mifflin Harcourt, 2014)
"In this outstanding picture book collection of poems by Newbery Honor-winning poet, Joyce Sidman ("Song of the Water Boatman," " Dark Emperor and Other Poems of the Night"), discover how animals stay alive in the wintertime and learn about their secret lives happening under the snow. Paired with stunning linoleum print illustrations by Rick Allen, that celebrate nature's beauty and power."--From the publisher.